THE IMPACT OF MACROECONOMIC VARIABLES ON INDONESIA ISLAMIC BANKS PROFITABILITY - Cupian Amzal (Jurnal Ekonomi dan Bisnis Islam | Journal of Islamic Economics and Business, 2016)
Economic development of  Indonesia has an important role in the growth of Islamic banking sector. It is clear that the Islamic banking sector in Indonesia needs a conducive economic situation to make a better performance. The objective of this study was to investigate  the influence of macroeconomic variables on the profit of Islamic Banks in Indonesia. Macroeconomic variables used in this study were Gross Domestic Product (GDP),  Inflation rate  and BI Rate (interest rate of the central bank of Indonesia).   In addition, Non Performing Financing (NPF) was included in this model to represent another determinant for banks in gaining profit. Econometric model  by formulating a multiple regression model was used to estimate the impact of GDP, BI Rate, Inflation rate and NPF  on the profit of Islamic banks.The results of this study showed that partially, all explanatory variables (GDP and BI Rate, Inflation Rate and NPF) have a significant effect on the Profit of Islamic Banks.Keywords: Macroeconomic variables, Islamic banks, Non Performing Financing